A role for clathrin in the sorting of vacuolar proteins in the Golgi complex of yeast. - Seeger, M (1992)
We have investigated the role of clathrin in vacuolar protein sorting using yeast strains harboring a temperature-sensitive allele of clathrin heavy chain (chc1-ts). After a 5 min incubation at the non-permissive temperature (37 degrees C), the chc1-ts strains displayed a severe defect in the sorting of lumenal vacuolar proteins. Sorting of a vacuolar membrane protein, alkaline phosphatase, and transport to the surface of a cell wall protein, was not affected at 37 degrees C. In chc1-ts cells incubated at 37 degrees C, secretion of the missorted lumenal vacuolar protein carboxypeptidase Y (CPY) was blocked by the sec1 mutation which prevents fusion of secretory vesicles to the plasma membrane. Unexpectedly, chc1-ts cells incubated for extended periods at 37 degrees C regained the ability to sort CPY. Cells carrying deletions of the CHC1 gene (chc1 delta) also sorted CPY to the vacuole even when subjected to temperature shifts. Vacuolar delivery of CPY in chc1 delta cells was not blocked by sec1 suggesting that transport does not occur by secretion and endocytosis. These results provide in vivo evidence that clathrin plays a role in the Golgi complex in sorting of vacuolar proteins from the secretory pathway. With time, however, yeast cells lacking functional clathrin heavy chains are able to adapt in a way that allows restoration of vacuolar protein sorting in the Golgi complex. These conclusions clarify previous studies of chc1 delta cells which raised the possibility that clathrin is not involved in vacuolar protein sorting.